Reconciling facts with fiction: Minimum wages in a post-Keynesian perspective - Arne Heise (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2017)
There has long been a discussion about the employment impact of minimum wages and this discussion has recently been renewed with the introduction of an economy-wide, binding minimum wage in Germany in 2015. In traditional reasoning, based on the allocational approach of modern labour market economics, it has been suggested that the impact is clearly negative on the assumption of a competitive labour market and clearly positive on the assumption of a monopsonistic labour market. Unfortunately, both predictions conflict with the empirical findings, which do not show a clear-cut impact of significant size in any direction.
Keywords: B50; E12; E23; J31; 330; Post-Keynesianism; minimum wage; aggregate demand; aggregate supply